Vegetal regulators increase the quality of atemoya fruits and recover the photosynthetic metabolism of stressed plants - Verotti, Tamara do Prado [UNESP]; Oliveira, Caroline Genari de [UNESP]; Parreiras, Nathalia de Souza [UNESP]; Moura Goncalves, Fabricio Custodio [UNESP]; Correa, Carla Veronica [UNESP]; Ferreira, Gisela [UNESP]; Campos, Felipe Girotto [UNESP]; Fernandes Boaro, Carmen Silvia [UNESP] (Springer, 2019)
Vegetal regulators such as auxin, cytokinin, and gibberellin were applied in different concentrations, through commercial mix, to Thompson variety of atemoya fruits to verify the effect of the regulators in the quality of healthy plants of atemoya fruit and its influence in the gas exchange of the stressed plants. The study was conducted with two experiments: the first experiment consisted in the application of the mix of auxin, cytokinin, and gibberellin with concentrations of 0, 200, 300, 400, and 600 mL ha(-1), during 14 days, for 5 months, in commercial orchard and in healthy plants. There were evaluated length, diameter, fresh mass of the peel, fresh mass of the pulp, and total fresh mass; fruits' volume, soluble solids and pH of the pulp, and number and fresh mass of the seeds. In the second experiment, the application of the regulators' mix in the concentrations that resulted in better quality of the fruits such as 300 and 400 mL ha(-1) was conducted in stressed plants to evaluate the recovery of the photosynthetic metabolism and of the physical-chemical quality of the fruits. In this experiment, the control treatment (without application of the mix) was conducted in the plants with good visual conditions and highest numbers of greener leaves, smaller leaves and yellowish leaves. The gas exchanges were conducted every 14 days, and when the fruits ripened, they were harvested for the measurement of ascorbic acid, soluble sugars, reducing sugars, sucrose, and starch. The concentrations of the mix of auxin, cytokinin, and gibberellin such as 300 and 400 mL ha(-1) improved the quality of the fruits and recovered the gas exchange of stressed plants without modifying the physical-chemical characteristics of its fruits, setting itself as an agricultural practice that is beneficial for the atemoya fruit cultivation.
Keywords: Auxin; Cytokinin; Gibberellin; Gas exchange; Post-harvest